INFLUENCE OF THE NOISE AND VIBRATION OF THE PUBLIC TRANSPORT (SUBWAY) ON THE HEALTH OF USERS (Fiep Bulletin - online, 2016)
Introduction: In the face of all kinds of environmental degradation, noise occupies a prominent place, and the noise was long regarded as a product of stress in the population. Objective: To determine the noise impact of the subway in the user's health. Methodology: It is a transversal, descriptive, explanatory, study whose initial sample, was composed by 100 users of the subway in the city of São Paulo of the lines: blue, red and green, that they set out to answer a form whose questions were used as variables in the study as well as measure the noise and vibration using as reference the levels of noise established by CONAMA Resolution n ° 1/90 establishing the criteria ABNT for noise emitted by the subway. The assessment was performed by the dosimeter method with the use of the sound level meter, the three lines of the São Paulo subway. The data after compiled were presented in tables and simple frequency charts expressed in numbers and percentages. Results: The results show that 37% of users feel stressed; 21% claim to have irritability; 12% have sleep disturbances; 10% feel tired; 9% had nausea frame; 6% muscle aches and 5% report having lost appetite. In relation to the express noises in decibels, the results show that the red line is 67dB; on the blue line are 107 dB and on the green line 88 dB. Thus, it can be concluded that the red line is the one that has less noise, is that you can buy to a conversation with normal sound. With regard to the consequences caused by noises, stress is more presented, which is the result of the absorption of noise pollution.
Keywords: Noise pollution; Noise; Vibration; Sound effects; Subway.